Appendectomy: Should it be Performed So Quickly?. Issue 1 (January 2016) - Jeon, Byeong Geon; Kim, Hyuk Jung; Jung, Kuk Hyun; Lim, Hye In; Kim, Sang Wook; Park, Jin Soo; Kim, Ki Ho; Kim, Il Dong
Controversy surrounds appendectomy timings and their effects on postoperative outcomes. This study evaluated the influence of hospital delays on perforation rates and complications in patients with acute appendicitis. From January 2008 to December 2013, the cases of 4148 consecutive patients who had undergone appendectomies for suspected appendicitis were reviewed. The patients' demographic data, times from symptom onset to hospital arrival (prehospital delay), times from hospital arrival to surgery (hospital delay), histological findings, and postoperative outcomes were documented. Perforation rates and complications were assessed at each time interval between symptom onset and surgery. Perforation rates and complications increased with longer prehospital delays, but no correlations were evident between hospital delays and perforation rates or between hospital delays and complications. Although delaying appendectomies for >18 hours had no statistically significant impact on perforation rates (25.3 vs 19.4%, P = 0.133), it caused more complications (8.7 vs 3.8%, P = 0.023) compared with cases delayed for 12 to 18 hours. Multivariate analyses determined that hospital delays were not associated with increased risks of perforation, complications, wound infections, or intra-abdominal abscesses. However, a >18-hour hospital delay was associated with a significantly increased risk of postoperative ileus (odds ratio = 2.94, 95% confidence interval = 1.17–7.41, P = 0.022). Hospital delays were not associated with significantly increased risks of perforation and complications. However, patients with perforated appendicitis had higher risks of developing postoperative ileus if hospital delays were >18 hours. Therefore, hospital delays of ≤18 hours are safe, but caution is required if delays are >18 hours.